2008
DOI: 10.2353/ajpath.2008.080518
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Melatonin in Experimental Uveitis

Abstract: Uveitis is a common ophthalmic disorder that can be induced in hamsters by a single intravitreal injection of bacterial lipopolysaccharide (LPS). To examine the therapeutic effects of melatonin on uveitis, a pellet of melatonin was implanted subcutaneously 2 hours before the intravitreal injection of either vehicle or LPS. Both 24 hours and 8 days after the injection, inflammatory responses were evaluated in terms of i) the integrity of the blood-ocular barrier, ii) clinical signs, iii) histopathological studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 53 publications
5
45
0
Order By: Relevance
“…16 Moreover, we showed that melatonin significantly attenuates biochemical, clinical, histological, ultrastructural, and functional alterations induced by experimental uveitis, and it preserves the BRB integrity. 49 As already mentioned, glucocorticoids induce and aggravate CSCR. The antagonism exerted by melatonin on the glucocorticoid response has been well established.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…16 Moreover, we showed that melatonin significantly attenuates biochemical, clinical, histological, ultrastructural, and functional alterations induced by experimental uveitis, and it preserves the BRB integrity. 49 As already mentioned, glucocorticoids induce and aggravate CSCR. The antagonism exerted by melatonin on the glucocorticoid response has been well established.…”
Section: Discussionmentioning
confidence: 93%
“…Five patients with chronic CSCR served as a control group. The mean age of control patients was 44 years old (range, [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], with the woman/man ratio being 1 : 4. The number of right and left eyes studied was also similar (3 right eyes and 2 left eyes).…”
Section: Resultsmentioning
confidence: 99%
“…These effects were less marked in the group treated with both LPS and propolis. This indicated that propolis may stimulate www.fhc.viamedica.pl repair of the outer nuclear layer of the neural retina; this hypothesis will be tested in a future study of propolis in chronic uveitis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Uveitis is an ophthalmic disorder that causes vision loss in developed countries (22,23) and is characterized by acute, recurrent, or persistent ocular inflammation, the breakdown of the blood-ocular barrier, and infiltration of leukocytes (24). The underlying causes of uveitis can vary.…”
mentioning
confidence: 99%